2017
DOI: 10.1371/journal.pone.0183040
|View full text |Cite
|
Sign up to set email alerts
|

Corneal confocal microscopy is a rapid reproducible ophthalmic technique for quantifying corneal nerve abnormalities

Abstract: PurposeTo assess the effect of applying a protocol for image selection and the number of images required for adequate quantification of corneal nerve pathology using in vivo corneal confocal microscopy (IVCCM).MethodsIVCCM was performed in 35 participants by a single examiner. For each participant, 4 observers used a standardized protocol to select 6 central corneal nerve images to assess the inter-observer variability. Furthermore, images were selected by a single observer on two occasions to assess intra-obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 22 publications
3
86
0
Order By: Relevance
“…To assess this, we used in vivo corneal confocal microscopy (CCM) to quantify corneal nerve morphology as an objective imaging end point for the extent of neurologic disease in FRDA. [12][13][14][15][16][17][18] The data demonstrate that quantification of corneal nerve morphology using CCM correlates well with the GAA repeat length, and SARA and FARS scores, supporting the concept that CCM can be used as a noninvasive, objective imaging biomarker to quantify neurologic deficits in FRDA.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…To assess this, we used in vivo corneal confocal microscopy (CCM) to quantify corneal nerve morphology as an objective imaging end point for the extent of neurologic disease in FRDA. [12][13][14][15][16][17][18] The data demonstrate that quantification of corneal nerve morphology using CCM correlates well with the GAA repeat length, and SARA and FARS scores, supporting the concept that CCM can be used as a noninvasive, objective imaging biomarker to quantify neurologic deficits in FRDA.…”
supporting
confidence: 53%
“…Healthy matched subjects were identified by advertisements. Written informed consent was obtained under Age at 1st symptom, yr N/A 11.5 ± 5.0 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) Age at diagnosis, yr N/A 14.7 ± 6.5 Duration from 1st symptom, yr N/A 13.0 ± 5.2 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) Duration from diagnosis, yr N/A 10.0 ± 5.4 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)…”
Section: Study Populationmentioning
confidence: 99%
“…51 Additionally, the application of a standardized approach as in the current study has recently been shown to have high intra-and interobserver reproducibility for all corneal nerve parameters. 52 We observed that there are focal losses in GCC volume (GCC FLV) in the macular area in very mild and mild NPDR in the presence of comparatively normal GCC and RNFL thickness. GCC FLV is similar in concept to pattern standard deviation of the Humphrey visual fields test, which indicates the local depressions and potholes in the entire GCC map after correcting for the overall depression of the topography of GCC thickness map.…”
Section: Discussionmentioning
confidence: 67%
“…Images were selected by a single expert in a masked fashion taking into account the quality, depth, and variability using an established protocol. 10,19 We quantified five corneal nerve parameters: corneal nerve fiber density (CNFD: total number of main nerves per square millimeter) (no./mm 2 ), corneal nerve branch density (CNBD: total number of branches per square millimeter) (mm/mm 2 ), corneal nerve fiber length (CNFL: total length of main nerves and nerve branches per square millimeter) (mm/mm 2 ), inferior whorl length (IWL: total length of nerves per square millimeter) (mm/mm 2 ), and average nerve fiber length (ANFL = CNFL + IWL/2) (mm/mm 2 ).…”
Section: Corneal Nervesmentioning
confidence: 99%